Behind Closed Gates: The Barriers to Self-Expression and Publication for Australian Young Adult Authors of OwnVoices Fiction. Issue 2 (June 2021) - Booth, Emily; Narayan, Bhuva
Abstract : This article based on an empirical study of Australian authors argues that, despite the OwnVoices movement gathering momentum in Australia, there are still barriers and limitations for authors from marginalised communities within the Australian publishing industry. This is due to power imbalances in publishing spaces which silence marginalised writers, limiting the availability of their books to teenage readers.